Use of Vaginal Hygiene Product, Physical Activity, Age at Marriage, Body Mass Index, and Female Infertility - Arifin, Ayu Kusuma Puspasari; Murti, Bhisma; Budihastuti, Uki Retno (Journal of Maternal and Child Health, 2016)
Background: Various products are common in the market for vaginal hygiene purpose, such as povidone iodine vaginal douche, extract of betel leaf, and other herbal internal vaginal hygiene products. However, it is hypothesized that these hygiene products may hamper female fertility. This study aimed to examine the effect of vaginal hygiene product use on female fertility, while controlling for the level of physical activity, age at marriage, and body mass index.Subjects and Method: This study was analytical-observational with case control design, conducted at Dr. Moewardi Hospital, Surakarta, Indonesia. The study population were women aged 15-49 years old. A total of 55 infertile women and 55 pregnant or post-partum women were selected as cases and controls, respectively, by using fixed diseases sampling. The dependent variable was infertility. The independent variables were external and internal use of vaginal hygiene product, level of physical activity, age at marriage, and body mass index (BMI). The data were analyzed using multiple logistic regression.Results: External use of vaginal hygiene product decreased the risk of infertility, but it was statistically non-significant (OR=0.62; 95%CI= 0.22 to 1.74; p=0.366). Internal use of vaginal hygiene product (OR=14.97; 95%CI= 1.66 to 135.16; p=0.016), heavy physical activity (OR=7.95; 95%CI= 1.54 to 41.08; p=0.013), age at marriage>29 years (OR=3.66; 95%CI= 0.68 to 19.76; p=0.131), BMI<18,5kg/m2(OR=1.62; 95%CI= 0.31 to 8.56; p=0.572), and BMI Ã¢â°Â¥ 25kg/m2(OR=23.17; 95%CI= 4.05 to 132.40; p<0.001) increased the risk of infertility.Conclusion: Internal use of vaginal hygiene product, heavy physical activity, age at marriage>29 years, underweight, and overweight, are risk factors of infertility in women. Women who use vaginal hygiene product internally should be aware that this practice significantly increased the risk of infertility.Keywords:Female infertility, vaginal hygiene product, physical activities, age at marriage, body mass indexCorrespondence: Ayu Kusuma Puspasari Arifin. Masters Program in Public Health, Sebelas Maret University. Email: puspasari.arifin@yahoo.comJournal of Maternal and Child Health (2016), 1(1): 41-52https://doi.org/10.26911/thejmch.2016.01.01.07